Evaluation of Driving Comparative Life Cycle Cost Assessment of Conventional and Electric Motorcycles in Indonesia: Monte Carlo Analysis - Yuniaristanto; Lsa Aldira Hafidza; Wahyudi Sutopo; Muhammad Hisjam (Jurnal Optimasi Sistem Industri, 2022)
The adoption of electric vehicles (EVs) is one of the solutions to reduce emission problems. Vehicle cost analysis is one of the keys to seizing the Indonesian market. As a consumer, it is not only the purchase price that needs to be considered, but the life cycle costs throughout ownership also need to be considered in the purchase. This study discusses the life cycle cost (LCC) of EVs in Indonesia, especially electric motorcycles (EMs), which will be compared with conventional motorcycles (CMs). In particular, this study aims to encourage the government's target for ownership of 2.1 million EMs in Indonesia by 2025. The novelty of this research is to develop a more comprehensive LCC model by considering the costs in terms of tangible and intangible to compare the two types of motorcycles using Monte Carlo simulation. This simulation is used to coordinate the behavioral uncertainty of motorcycle users. As a result, the value of an EM is more economical than CM for various users. The average value percentage of EMs is lower than CMs by 45% (IDR 30,6 million). In addition, several scenarios are also analyzed to maximize consumer welfare in Indonesia.